Phonon transport in nanowire with contacts : size and doping - Li, Jing (2013)
The phonon transport in Lennard-Jones silicon wire with contacts is investigated using non-equilibrium Green’s function. With the size decreasing, the significant reduction in the number of phonon modes leads to a smaller thermal conductance density. The dopant (Ge) atoms are used to substitute the atom in the wire to study the doping effect. For thin wire, its thermal conductance is very sensitive to the location of dopants. It is also found that the interior atom substitution has more impact on the thermal conductance over surface atom; substitution near contact surface reduces thermal conductance significantly; thermal conductance is suffering a 10%–20% variation due the random distribution of dopants; 17% of Ge content is sufficient to reduce thermal conductance by 80%.